PENGUATAN LITERASI KEAGAMAAN DAN PERUBAHAN KARAKTER NAPITER - Jufri Naldo (Harmoni, 2022)
One thing former terrorism convicts experience when they are free from prison is their indignity to return to society. On the one hand, they feel discriminated against due to their social status as a terrorist, on the other hand, their religious understanding has not changed too much because the deradicalization program in religious science education provided has not been maximized. As a result, many of the former terrorism convicts after their release returned to the ideology of radical groups and repeated acts of terror. This article aims to find the ideal form of religious formation needed by terrorism convicts, so that they can change their character after they leave custody. This research is qualitative using phenomenological methods, data obtained through interviews with terrorism convicts. The results revealed that strengthening religious literacy in deradicalization programs for terrorism convicts could change their character to normal and better. Through the upbringing of religious awareness provided by experts and sustained by diverse religious readings while in prison, it gives them broad insights. So that after punishment, they returned to society with a new character.